2002
DOI: 10.1089/105072502320908330
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction and Autoimmunity in Infertile Women

Abstract: A prospective study was undertaken in 438 women (ages, 32 +/- 5 years) with various causes of infertility, and in 100 age-matched (33 +/- 5 years) healthy parous controls with the aim of assessing the prevalence of autoimmune thyroid disease (AITD) and hitherto undisclosed alterations of thyroid function. Female origin of the infertility was diagnosed in 45% of the couples, with specific causes including endometriosis (11%), tubal disease (30%), and ovarian dysfunction (59%). Male infertility represented 38% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
157
4
20

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(186 citation statements)
references
References 26 publications
5
157
4
20
Order By: Relevance
“…women compared to non-positive ones. 63 Previously menstrual disorders including particularly oligomenorrhea was reported as 50% in people with hyperthyroidism, but Krassas et al found that the rate is around 21.5 % in thyrotoxicosis. 4,64 Mean radioactive iodine (370 MBq) dose used in treating hyperthyroidism is curative and it doesn't affect gonadal performance.…”
Section: Hyperthyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…women compared to non-positive ones. 63 Previously menstrual disorders including particularly oligomenorrhea was reported as 50% in people with hyperthyroidism, but Krassas et al found that the rate is around 21.5 % in thyrotoxicosis. 4,64 Mean radioactive iodine (370 MBq) dose used in treating hyperthyroidism is curative and it doesn't affect gonadal performance.…”
Section: Hyperthyroidismmentioning
confidence: 99%
“…In hypothyroidism, both the local effect of thyroid hormones on these receptors and prevention of release of pulsatile GnRH from hypothalamus lead to failure of healthy ovulation and prevent formation of high quality oocytes. 15 Concurrently, corpus luteum insufficiency due to disruption of LH release and hyperpolactineamia due to increased TRH release may also increase negative influences over normal menstrual cycle. 10,14 In hypothyroidism, even though elevated TSH may reduce sex hormone binding protein (SHBP), increasing free testosterone and estradiol level, total serum level of these hormones are usually low.…”
Section: Hypothyroidismmentioning
confidence: 99%
“…A positive correlation was found in early follicular phase between basal TSH, LH and T; moreover women with elevated TSH response to TRH had lower pregnancy rate than women with normal TSH response (Gerhard et al, 1991). In a controlled prospective study of 438 women with infertility of various origin, the median TSH levels were significantly higher than controls (Poppe et al, 2002). Moreover more frequent miscarriages were observed in women with higher basal TSH levels, irrespective of the presence of AITD (Raber et al, 2003).…”
Section: Hypothyroidism and Female Infertilitymentioning
confidence: 92%
“…Also, TSH is indirectly involved in endometrial pathology. A higher risk to develop endometriosis was reported in patients with associated thyroid autoimmunity (Poppe et al, 2002). Finally, hCG has been tested for impairing the painful endometrial symptoms (Huber et al, 2004).…”
Section: Endometriosismentioning
confidence: 99%